Contributions of multidisciplinary peer observation to lecturers’ reflective practices - Mouraz, Ana (2021)
The goals of this paper are to explain the extent to which multidisciplinary peer observation practices may improve reflection among lecturers concerning their pedagogical practices. and identify the kind of reflection it improves. In this sense, the paper presents a study with the objective of determining the importance that lecturers give to reflection upon their pedagogical practices as they are engaged in a multidisciplinary peer observation program. Data were collected through interviews and observation records. The results suggest a confirmation, among other aspects, of a commitment to a reflective discourse both in the work carried out by lecturers and as it concerns the pedagogical issues of their training.